2021
DOI: 10.3389/fmed.2021.801078
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Patients With Idiopathic Inflammatory Myopathies in Slovenia

Abstract: Background: Idiopathic inflammatory myopathies (IIMs) are rare systemic diseases associated with significant morbidity and mortality. The aim of our study was to estimate for the first time the survival of IIM patients in Slovenia.Methods: We included IIM patients diagnosed between January 2005 and December 2020 and followed at two secondary/tertiary rheumatology centers in the country. To study survival/mortality the censor date of April 14 2021 was set. Kaplan–Meier analysis and standardized mortality ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Organ involvement also differ considerably between cohorts. In our study, cardiac, lung and GI involvement affected 23.7%, 38.5% and 36.5% of the patients, respectively while Slovenian and Italian cohorts reported much lower cardiac involvement (11.5% and 14.3%), and Spanish REMICAM cohort reported lower ILD prevalence (27%) (8,12,15). A Japanese cohort reported almost a doble ILD prevalence (64%) and lower cardiac and GI involvement (17% and 21%, respectively) (14).…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations
“…Organ involvement also differ considerably between cohorts. In our study, cardiac, lung and GI involvement affected 23.7%, 38.5% and 36.5% of the patients, respectively while Slovenian and Italian cohorts reported much lower cardiac involvement (11.5% and 14.3%), and Spanish REMICAM cohort reported lower ILD prevalence (27%) (8,12,15). A Japanese cohort reported almost a doble ILD prevalence (64%) and lower cardiac and GI involvement (17% and 21%, respectively) (14).…”
Section: Discussionmentioning
confidence: 44%
“…As expected, most patients were treated with a combination of steroids and immunosuppressive drugs, with azathioprine being the most common (73.4%). There were some differences in drug preferences between studies, with other authors favouring the use of methotrexate (12,15), which may be due to drug policies, but also differences in organ involvement. In our study, we found that mortality rate was lower in patients who were ever given MMF, whereas those who received cyclophosphamide at anytime had higher mortality rates.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Holc demonstrated that Slovenian patients with idiopathic inflammatory myopathy (IIMs) had higher mortality rates compared to the general population in Slovenia during a 16-year observation period. The first year following diagnosis was characterized by 7 times higher mortality rate [ 155 ]. Vojinovic and colleagues found no close link between creatinine kinase (CK) levels, various types of IIM, and myositis-specific autoantibodies.…”
Section: Autoimmune and Rheumatic Diseases During Auto13: (Diseases 1–9)mentioning
confidence: 99%